Visualizing Affordances of Everyday Objects Using Mobile Augmented Reality to Promote Safer and More Flexible Home Environments for Infants - Miho Nishizaki (Advances in Science, Technology and Engineering Systems Journal, 2018)
This study presented a prototype augmented reality (AR) application that helps visualize the affordances of everyday objects for infants in their home environments to prevent accidents and promote development. To detect and visualize affordances, we observed 16 infants regarding how they perceive and handle common objects from 4 to 12 months of age in their homes in Tokyo, Japan and in Lisbon, Portugal. Based on the longitudinal observation data, we developed an AR application for handheld devices (iPhone and iPad) and tested two types of vision-based markers. Ten types of basic objects were selected from the results of the observation and embedded into the AR markers. AR contents illustrated infants’ actions toward objects based on actual video data recorded for security purposes. To confirm the prototype’s advantages and improvements, informal user interviews and user tests were conducted. The results demonstrated that the prototype reveals the relationship between infants and their home environments, what kinds of objects they have, how they perceive objects, and how they interact with these objects. Our study demonstrates the potential of this application’s AR contents to enable adults to better understand infants’ behavior towards objects by considering the affordances of everyday objects. Specifically, our app assists in improving the perspective of adults who live with infants and promotes the creation of more flexible and safer environments.
Keywords: Augmented Reality (AR); Affordance; Visualization; Accident; Development; Infant